Distinguishing intrahepatic cholangiocarcinoma from poorly differentiated hepatocellular carcinoma using precontrast and gadoxetic acid-enhanced MRI - Yoshiki Asayama; Akihiro Nishie; Kousei Ishigami; Yasuhiro Ushijima; Yukihisa Takayama; Nobuhiro Fujita; Yuichiro Kubo; Shinichi Aishima; Ken Shirabe; Takashi Yoshiura; Hiroshi Honda (Diagnostic and Interventional Radiology, 2015)

(untitled)
PURPOSEWe aimed to gain further insight in magnetic resonance imaging characteristics of mass-forming intrahepatic cholangiocarcinoma (mICC), its enhancement pattern with gadoxetic acid contrast agent, and distinction from poorly differentiated hepatocellular carcinoma (pHCC).METHODSFourteen mICC and 22 pHCC nodules were included in this study. Two observers recorded the tumor shape, intratumoral hemorrhage, fat on chemical shift imaging, signal intensity at the center of the tumor on T2-weighted image, fibrous capsule, enhancement pattern on arterial phase of dynamic study, late enhancement three minutes after contrast injection (dynamic late phase), contrast uptake on hepatobiliary phase, apparent diffusion coefficient, vascular invasion, and intrahepatic metastasis.RESULTSLate enhancement was more common in mICC (n=10, 71%) than in pHCC (n=3, 14%) (P < 0.001). A fat component was observed in 11 pHCC cases (50%) versus none of mICC cases (P = 0.002). Fibrous capsule was observed in 13 pHCC cases (59%) versus none of mICC cases (P < 0.001). On T2-weighted images a hypointense area was seen at the center of the tumor in 43% of mICC (6/14) and 9% of pHCC (2/22) cases (P = 0.018). Other parameters were not significantly different between the two types of nodules.CONCLUSIONThe absence of fat and fibrous capsule, and presence of enhancement at three minutes appear to be most characteristic for mICC and may help its differentiation from pHCC.